Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) x - 36 + 12 = - x+ 10
=> x + x = 10 + 24
=> 2x = 34
=> x = 34/2 = 17
2) (x + 15) - (11 - x) = (-2)2
=> x + 15 - 11 + x = 4
=> 2x = 4 - 4
=> 2x = 0
=> x = 0
3) 40 - 4x2 = (-6)2
=> 40 - 4x2 = 36
=> 4x2 = 40 - 36
=> 4x2 = 4
=> x2 = 1
=> x = \(\pm\)1
4) (-50) + 10x2 = (-25) x |-2|
=> -50 + 10x2 = -50
=> 10x2 = -50 + 50
=> 10x2 = 0
=> x2 = 0
=> x = 0
5) |x + 1| = 2020
=> \(\orbr{\begin{cases}x+1=2020\\x+1=-2020\end{cases}}\)
=> \(\orbr{\begin{cases}x=2019\\x=-2021\end{cases}}\)
6) (x + 1)5 + 8 = 0 (xem lại đề)
7) (-20) + x3 : 16 = -24
=> x3 : 16 = -24 + 20
=> x3 : 16 = -4
=> x3 = -4 . 16
=> x3 = -64 = (-4)3
=> x = -4
9) x14 = x17
=> x14 - x17 = 0
=> x14(1 - x3) = 0
=> \(\orbr{\begin{cases}x^{14}=0\\1-x^3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
10) (-36) + (1 - x)2 = 0
=> (1 - x)2 = 36
=> (1 - x)2 = 62
=> \(\orbr{\begin{cases}1-x=6\\1-x=-6\end{cases}}\)
=> \(\orbr{\begin{cases}x=-5\\x=7\end{cases}}\)
\(\left(3x-15\right)^7=0\Rightarrow3x-15=0\)
\(\Rightarrow3x=15\)
\(\Rightarrow x=5\)
\(4^2.x-6=1\Rightarrow16.x=7\)
\(\Rightarrow x=\frac{7}{16}\)
a, ( x2 + 5 ) . ( x2 - 25 ) = 0
Vì \(x^2+5\ne0\forall x\Rightarrow\left(x^2+5\right)\left(x^2-25\right)=0\Leftrightarrow x^2-25=0\)
\(\Leftrightarrow\left(x-5\right)\left(x+5\right)=0\Leftrightarrow\orbr{\begin{cases}x-5=0\\x+5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
Vậy x = -5; 5
92.(5x-2)3=37
81.(5x-2)3=2187
(5x-2)3=2187:81
(5x-2)3=27
suy ra :33=27
a) ( x2 + 5 )( x2 - 25 ) =0
=> x2 + 5 =0 hoặc x2 -25 =0
=> x = \(\sqrt{-5}\) hoặc x = 5
có phải câu hỏi là x2-10x+25=0 ko
Đề là x2-10x+25=0 hả
<=>(x-5)2=0
<=>x=5